Magnetic Resonance Imaging Findings of Intraspinal Tuberculoma in Children - Zhou, Yirui; Qin, Yong; Mu, Tong; Zheng, Helin; Cai, Jinhua (Frontiers in Neurology, 2022)
Background and Purpose Intraspinal tuberculoma is a rare disease in children, and its imaging findings have been described in only a few case reports. This study aimed to investigate the magnetic resonance imaging (MRI) features of pediatric intraspinal tuberculoma and to explore the possible pathogenesis of the disease. Materials and Methods The clinical and MRI data of 24 child patients with intraspinal tuberculoma (such as 6 cases of intramedullary tuberculoma, 8 cases of intradural extramedullary tuberculoma, and 10 cases of epidural tuberculoma) were retrospectively analyzed. All patients underwent plain and contrast-enhanced MR scans. The diagnosis was confirmed by surgical pathology or by antituberculous treatment and follow-up data. Results Intramedullary tuberculoma had a round shape, while intradural extramedullary tuberculoma and epidural tuberculoma presented long-fusiform or en plaque shapes. Regarding MRI signals, intramedullary tuberculoma and extramedullary tuberculoma were mainly isointense on T1-weighted imaging (T1WI) and hypointense or isointense on T2WI. Rim enhancement was observed in intramedullary tuberculoma, and marked homogeneous enhancement was dominant in extramedullary tuberculoma. Ten (10/24) tuberculomas occurred during antituberculous therapy, with intradural extramedullary tuberculoma accounting for 7 cases (7/8), which was significantly more frequent than intramedullary tuberculoma (1/6) or epidural tuberculoma (2/10). Conclusion MRI is important in the diagnosis of intraspinal tuberculoma, which is characterized by isointensity on T1WI, isointensity, or hypointensity on T2WI, and rim or obvious homogeneous enhancement. Some intraspinal tuberculomas, especially intradural extramedullary tuberculomas, might be associated with the “paradoxical response” mechanism during the tuberculosis treatment.